2021
DOI: 10.3897/neobiota.67.58038
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of biological invasions within North America

Abstract: Invasive species can have severe impacts on ecosystems, economies, and human health. Though the economic impacts of invasions provide important foundations for management and policy, up-to-date syntheses of these impacts are lacking. To produce the most comprehensive estimate of invasive species costs within North America (including the Greater Antilles) to date, we synthesized economic impact data from the recently published InvaCost database. Here, we report that invasions have cost the North American econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 69 publications
1
47
0
3
Order By: Relevance
“…Most costs stemmed from direct damage rather than management spending and principally impacted the agriculture sector. This dominance of damage-related costs over management aligns with trends in other geographic regions worldwide (Crystal-Ornelas et al 2021;Haubrock et al 2021a;Heringer et al 2021;Liu et al 2021). Invasion impacts in the UK were largely driven by animals, which were both the most studied and costliest taxa.…”
Section: Question 1: Invasion Costs Distributions Through Space and Sectorssupporting
confidence: 67%
“…Most costs stemmed from direct damage rather than management spending and principally impacted the agriculture sector. This dominance of damage-related costs over management aligns with trends in other geographic regions worldwide (Crystal-Ornelas et al 2021;Haubrock et al 2021a;Heringer et al 2021;Liu et al 2021). Invasion impacts in the UK were largely driven by animals, which were both the most studied and costliest taxa.…”
Section: Question 1: Invasion Costs Distributions Through Space and Sectorssupporting
confidence: 67%
“…Management costs were similarly very low in Central and South America (2.1%, Herigner et al 2021). In other continents, management expenses were always higher than in Asia, yet consistently much lower than damage and loss costs: Africa (27%, Diagne et al 2021), Europe (16%, Haubrock et al 2021), or North America (<20%, Crystal-Ornelas et al 2021). This suggests the necessity of increasing funding for invasion management in Asia.…”
Section: Discussionmentioning
confidence: 96%
“…Compared to other regions, Central and South America have higher accumulated costs than Africa (USD 18.2 billion; Diagne et al 2021b) and a similar cost to that found in Europe when we used the same inclusion criteria, considering low reliability or potential costs (USD 140.2 billion; ). However, Central and South America have lower costs than North America and Asia (USD 1.26 trillion and USD 432.6 billion, respectively; Crystal-Ornelas et al 2021;Liu et al 2021). These differences were not entirely surprising considering the lower number of invasive alien species in Central and South America compared with North America (van Kleunen et al 2015;Pyšek et al 2019), as well as the research deficit in invasion biology in Central and South America (Bellard and Jeschke 2015), which can negatively affect the number of reported costs to the continents.…”
Section: General Patternsmentioning
confidence: 99%